The immune response to Mycobacterium tuberculosis in HIV-infected and uninfected adults in Uganda: application of a whole blood cytokine assay in an epidemiological study. - Elliott, A; Hurst, T; Balyeku, M; Quigley, M; Kaleebu, P; French, N; Biryahwaho, B; Whitworth, J; Dockrell, H; Hayes, R (1999)
SETTING: Out-patient clinic, Entebbe, Uganda. BACKGROUND: It has been proposed that 'type 1' cytokines are essential in protective immunity to Mycobacterium tuberculosis and that suppression of 'type 1' or a switch to a 'type 2' profile is deleterious. We employed a simple assay to examine whether the dependence of the immunological responses to mycobacterial antigens on a range of explanatory factors could be determined in a population where tuberculosis is endemic. OBJECTIVE: To determine the relationship between the tuberculin skin test response and cytokine profile, and the effect of human immunodeficiency virus (HIV) infection. DESIGN: A cross-sectional study of 97 Ugandan adults (22 HIV-positive, 75 HIV-negative). Whole blood was stimulated in vitro using mycobacterial antigens (purified protein derivative [PPD] and culture filtrate proteins [CFP]). 'Type 1' cytokines (gamma interferon [IFN-gamma] and interleukin-2 [IL-2]), 'type 2' cytokines (IL-5 and IL-10) and tumour necrosis factor alpha (TNF-alpha) were measured in culture supernatants. RESULTS: Among HIV-negative subjects, a positive tuberculin skin test was associated with type 1 or mixed (type 1 + type 2) cytokine production, but a positive IFN-gamma response also occurred in a proportion of tuberculin skin test negative subjects (36% for PPD, 17% for CFP). In association with HIV infection, IFN-gamma responses to mycobacterial antigens were profoundly impaired (odds ratio [OR] 0.10 for PPD, 0.06 for CFP, P< or =0.001), but production of IL-2, IL-5 and TNF-alpha was relatively sustained, and IL-10 increased or sustained (OR 3.97 for PPD, P = 0.01, 1.14 for CFP, P = 0.99). CONCLUSION: The type 1/type 2 cytokine balance was not defined by the tuberculin skin test response, and may have a closer relation to protective immunity. IFN-gamma production was strikingly impaired in association with HIV infection, while production of type 2 cytokines was sustained or increased. Use of a simple assay allowed a large sample of subjects to be examined, producing epidemiologically meaningful results.